Trail Running vs. Adequate Physical Activity on Physical Fitness, Vascular Function, and Cognition in Middle-Aged Office Workers - Siraprapa Panthong; Supawit Ittinirundorn; Wirungrong Nualpech; Kanokporn Leelartapin; Hirofumi Tanaka; Daroonwan Suksom (Physical Activity and Health)
Background: The dose-response relationship between exercise and its benefits is described by a biphasic response following the principle of hormesis. This information is particularly important for office workers who tend to remain sedentary during working hours. Aim: To evaluate a variety of health-related physical fitness, peripheral and cerebral vascular function, and cognition of middle-aged male office workers who had been regularly performing adequate physical activity or trail running. Methods: We studied two groups of middle-aged male office workers: one with moderate physical activity levels (Adequate PA, 40.5 ± 3.5 years, n = 14) and another who performed trail running on a regular basis (Trail runners, 40.2 ± 3.2 years, n = 15). Comprehensive measures of health-related physical fitness, peripheral and cerebral vascular function, and cognition were assessed. Results: Trail runners exhibited lower body fat percentage, while displaying higher aerobic fitness and muscle strength and endurance than Adequate PA (all p < 0.05). Arterial stiffness (as assessed by pulse wave velocity), wall thickness, and flow-mediated dilatation (FMD) were more favorable in Trail runners than in Adequate PA (all p < 0.05). A moderate correlation was observed between FMD and the level of physical activity (r = 0.53, p = 0.003). Measures of cognitive function were not different between the groups. Following the mental stress tests, the pulsatility index of the middle cerebral artery was lower in Trail runners than in Adequate PA (p < 0.05). Conclusion: Male office workers who regularly participate in trail running demonstrate more favorable health-related physical fitness and peripheral and cerebral vascular function compared with their office working peers with moderate or adequate physical activity.